Perilaku Pencegahan Covid-19 Pada Ibu Hamil - Astrida Budiarti; Ghitha Putri Immarta Dewi; Puji Hastuti; Muh. Zul Azri (Indonesian National Nurses Association (INNA) of Central Java, 2021)
Covid-19 is a virus that may attack all groups. One amongst the groups at risk is pregnant women. Being a vulnerable group, pregnant women must behave in keeping with health protocols. The aim of this study was to work out the knowledge, attitudes and behavior of preventing COVID-19 in pregnant women. The research design is descriptive analysis, with a cross-sectional approach. Samples of 74 pregnant women were taken by a purposive sampling method. The independent variable is COVID-19 prevention behavior. The variable dependent are knowledge and attitude to preventing COVID-19. Test analysis using the Chi-square test and Fisher's exact test. The results of the study show that the majority pregnant women have good knowledge of preventing Covid-19 (83.8%), have a negative attitude of preventing Covid-19 (58.1%), and 68.9% have behavior that supports the prevention of Covid-19. There is a relationship between knowledge and behavior of pregnant women in preventing COVID-19 with a p-value is 0.006 and there is a relationship between attitudes and behavior of pregnant women in preventing COVID-19 with a p-value is 0.018. The results of this study indicate that there are still behaviors that aren't in accordance with health protocols. Continuing education is required for pregnant women by leaflets, posters, electronic and online educational media, also as handwashing facilities at health care facilities. Additionally, government support is required to manage policies within the application of health protocols in order that Covid-19 prevention behavior is high and therefore the risk of Covid-19 events are controlled.Keyword: Behavior, Kvowledge, Attitude, Pregnant women, Covid-19